Primary immunodeficiency-related genes and varicella-zoster virus reactivation syndrome: a Mendelian randomization study - Wang, Hao; Chen, Guanglei; Gong, Qian; Wu, Jing; Chen, Peng (Frontiers in Immunology, 2024)
Background: Currently, evidence regarding the causal relationship between primary immunodeficiency-related genes and varicella-zoster virus reactivation syndrome is limited and inconsistent. Therefore, this study employs Mendelian randomization (MR) methodology to investigate the causal relationship between the two.Methods: This study selected 110 single-nucleotide polymorphisms (SNPs) of primary immunodeficiency-related genes as instrumental variables (IVs). Genetic associations of primary immunodeficiency-related genes were derived from recent genome-wide association studies (GWAS) data on human plasma protein levels and circulating immune cells. Data on genes associated with varicella-zoster virus reactivation syndrome were obtained from the GWAS Catalog and FINNGEN database, primarily analyzed using inverse variance weighting (IVW) and sensitivity analysis.Results: Through MR analysis, we identified 9 primary immunodeficiency-related genes causally associated with herpes zoster and its subsequent neuralgia; determined causal associations of 20 primary immunodeficiency-related genes with three vascular lesions (stroke, cerebral aneurysm, giant cell arteritis); revealed causal associations of 10 primary immunodeficiency-related genes with two ocular diseases (retinopathy, keratitis); additionally, three primary immunodeficiency-related genes each were associated with encephalitis, cranial nerve palsy, and gastrointestinal infections.This study discovers a certain association between primary immunodeficiency-related genes and varicella-zoster virus reactivation syndrome, yet further investigations are warranted to explore the specific mechanisms underlying these connections.